Pengaruh Daya Tarik Wisata, Citra Destinasi Dan Electronic Word Of Mouth (E-Wom) Terhadap Minat Kunjungan Ulang (Studi Pada Museum Mulawarman) - Armianti, Cindi; Palinggi, Yonathan; Ningsih, Kartina Eka (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2024)
This research aims to analyze the influence of tourist attractions, destination image and electronic word of mouth (E-WOM) on Revisit Intention (Study at the Mulawarman Museum). The population in this study were visitors to the Mulawarman Museum in Tenggarong. The research sample was 97 visitors to the Mulawarman Museum. Sampling used the Simple Random Sampling technique and the data analysis tool used Multiple Linear Regression using SPSS Version 26 software. Based on the research results, it shows that (1) Tourist Attraction, Destination Image and Electronic Word of Mouth simultaneously have a significant effect on Revisit Intention. (2) Tourist Attraction does not have a positive and significant effect on Revisit Intention. (3) Destination image has a positive and significant effect on Revisit Intention. (4) Electronic Word of Mouth has a positive and significant effect on Revisit Intention. (5) Destination image has a dominant influence on Revisit Intention.